1997
DOI: 10.1007/s004600050178
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous alloying of gold clusters into nanometer-sized antimony clusters

Abstract: Alloying behavior of gold into nm-sized amorphous antimony (a-Sb) clusters has been studied by transmission electron microscopy (TEM), employing gold clusters in contact with a-Sb clusters. In order to produce gold clusters on individual a-Sb clusters, a-Sb clusters on an amorphous carbon film were cooled down to 96 K, and gold was then condenced on the film. When gold clusters in contact with a-Sb clusters are gradually heated from 96 to 290 K, dissolution of gold into a-Sb clusters sets in around 200 K and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…8. matched exactly with that of gold reported by Yasuda and Mori [17]. All analyses prove that the product is pure gold nanoparticles in the metal basis.…”
Section: Gold Extraction and Synthesis Of The Nanoparticlessupporting
confidence: 83%
See 1 more Smart Citation
“…8. matched exactly with that of gold reported by Yasuda and Mori [17]. All analyses prove that the product is pure gold nanoparticles in the metal basis.…”
Section: Gold Extraction and Synthesis Of The Nanoparticlessupporting
confidence: 83%
“…The EDS analysis showed that the particles consist of pure gold. Nearestneighbor lattice spacing was calculated as 0.288 by the average value of 20 atomic lines, which was confirmed as a gold (1 1 1) lattice [17]. In addition, the SAED diffractogram in Fig.…”
Section: Gold Extraction and Synthesis Of The Nanoparticlesmentioning
confidence: 99%
“…Rapid, spontaneous mixing has also been observed for many other binary nanocluster systems, e.g., Au−Ni, Au− Zn, Au−Al, Au−Sn, and In−Sb. ,, Yasuda and Mori also investigated the dissolution of Au atoms into amorphous Sb clusters from Au clusters deposited onto a film containing preformed a-Sb clusters . Alloying occurs at relatively low temperatures (onset at around 200 K), with an activation barrier of approximately 0.5 eV.…”
Section: 1 Fast Intermixing Kinetics Of Cu−au Clustersmentioning
confidence: 96%
“…Alloying occurs at relatively low temperatures (onset at around 200 K), with an activation barrier of approximately 0.5 eV. At first, amorphous Au−Sb nanoparticles form, until the gold concentration reaches the stoichiometric composition of AuSb 2 , when the amorphous clusters crystallize into ordered AuSb 2 nanocrystals . Shimizu and colleagues also investigated rapid mixing in binary 4d metal nanoalloys (e.g., Ru−Mo, Mo−Nb, and Mo−Zr) 208 using Pettifor's SMATB-type model potential .…”
Section: 1 Fast Intermixing Kinetics Of Cu−au Clustersmentioning
confidence: 99%
“…20 nm) could occur through diffusion initiated by an electron beam at 200 kV for 30-60 minutes. [19][20][21][22][23][24] For smaller Ag and Au NPs (B3 and 7.5 nm), sintering was observed in the HR-TEM chamber under the action of an electron beam, which was accompanied by rearrangement of its crystal structure. 25 The low phase stability of nanoparticles can lead not only to melting and sintering but also to sublimation.…”
Section: Introductionmentioning
confidence: 99%